Spellbound : fantasy stories - Jones, Diana Wynne (Boston : Kingfisher, 2007)
A collection of eighteen short stories and excerpts from longer works of classic and contemporary fantasy by such authors as Jane Yolen, C.S. Lewis, L. Frank Baum, and E. Nesbit.
The peasant and the devil / the Brothers Grimm -- Boris Chernevsky's hands / Jane Yolen -- The hobgoblin's hat / Tove Jansson (from Finn family Moomintroll) -- Ully the piper / Andre Norton -- Milo conducts the dawn / Norton Juster (from The phantom tollbooth) -- Who goes down this dark road? / Joan Aiken -- The house of Harfang / C.S. Lewis (from The silver chair) -- Martha in the witch's power / K.M. Briggs (from Hobberdy Dick) -- Abu Ali meets a dragon / Noel Langley (from The land of green ginger) -- The box of delights / John Masefield (an extract) -- The amazing flight of the gump / L. Frank Baum (from The land of Oz) -- On the great wall / Rudyard Kipling (from Puck of Pook's Hill) -- The waking of the kraken / Eva Ibbotson (from Which witch?) -- The caves in the hills / Elizabeth Goudge (from Henrietta's house) -- Bigger than the baker's boy / E. Nesbit (from Five children and it) -- Jermain and the sorceress / Patricia C. Wrede (from The seven towers) -- Una and the red cross knight / Andrew Lang (from The red book of romance) -- What the cat told me / Diana Wynne Jones.
Angela Misa
Keywords: Children's stories; Fantasy fiction; Short stories; Fantasy